Pathogenesis of Intoxication in Hemorrhagic Hypotension (Experimental Study) - T. P. Khramykh; V. T. Dolgikh (Общая реаниматология, 2008)
Objective: to reveal the toxicity of unpaired abdominal organs and portal venous blood, which would appraise the actual contribution of each organ to the development of endotoxemia in the presence of hemorrhagic hypotension. Materials and methods: experiments were carried out on 50 outbred albino male rats and hemorrhagic hypotension was simulated in 40 animals. Following 15, 30, and 60 min and 2 hours, the liver, spleen, and intestine were taken and used to prepare homogenates whose toxicity was studied by the procedure developed by N. I. Gabriyelyan et al. The levels of oligopeptides (OP) were measured in the portal venous blood by the Lowry method and those of low and median molecular-weight substances (LMMWS) were separately determined in the whole blood and plasma by chemiluminescence. The significance of mean value differences was determined using the paired Student test and the unpaired Wilcoxon test. Results. The maximum LMMWS increment was established to be in the homogenates of the bowel, its large portion in particular. However, a decrease in LMMWS levels was revealed in later periods, which was indicative of a rapid intestinal adaptation to hypoperfusion. The progressive rise in the portal venous blood concentrations of LMMWS and OP was caused by altered intestinal wall permeability and bacterial translocation, followed by hepatic damage with the substantial activation of the prooxidative system and with the concurrent decrease in the antioxidative activity, as well as in the phagocytic activity of leukocytes. The spleen and liver showed the increased compensatory biotransformation of endotoxins and their elimination from the body. In the late periods, these organs acted as a source of LMMWS. At the same time, no rise and a further reduction in leukocytic phagocytic activity suggest that the latter is inhibited by portal venous blood toxins. Conclusion: Evaluation of the time course of changes in the values of intoxication, the rate of free radical oxidation processes, the phagocytic activity of leukocytes, as well as the relationship of these parameters are of practical value for the determination of further prognosis in hemorrhagic hypotension. Key words: hemorrhagic hypotension, low and median molecular-weight substances, oligopeptides, free radical oxidation, portal vein.